1998
DOI: 10.2355/isijinternational.38.36
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Additives in BaO-BaF2-MnO Slag on Phosphate and Manganese Capacities.

Abstract: The effects of various additives (CaO, MgO, Si0=, CaF, and Al~0,) According to Reactions (2) and (3) Table l). This slag systern can also meet the requirements of dephosphorizing ferro manganese. 3.2.BaO-CaO-BaF2-MnO SystemThe distribution ratios of phosphorus and manganese between BaOCaO-BaF2-MnO slags and MnFe-C-P melts at 1 300'C and po,=9'62 x 10 18 atm are plotted against the CaOcontent in Fig. 3 Vol. 38 (1998)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…Liu et al found that the increase in BaF 2 content in the BaO‐BaF 2 ‐MnO slag enhances the activity coefficient of MnO in the melts. They also mentioned that the CaF 2 in the BaO‐MnO slag is partly transformed to BaF 2 in the slag according to the following reaction:false(italicCaF2false)+false(BaOfalse)=false(CaOfalse)+false(italicBaF2false)…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al found that the increase in BaF 2 content in the BaO‐BaF 2 ‐MnO slag enhances the activity coefficient of MnO in the melts. They also mentioned that the CaF 2 in the BaO‐MnO slag is partly transformed to BaF 2 in the slag according to the following reaction:false(italicCaF2false)+false(BaOfalse)=false(CaOfalse)+false(italicBaF2false)…”
Section: Resultsmentioning
confidence: 99%
“…4 by plotting the phosphate capacity against the MnO to SiO 2 ratio. 8,[19][20][21] It is interesting that the phosphate capacity is not affected by MnO to SiO 2 ratio in the slags investigated. It increases only as the temperature decreases, viz.…”
Section: ϫmentioning
confidence: 99%
“…It increases only as the temperature decreases, viz. the phosphate capacity decreases in order of BaO-BaF 2 -MnO-SiO 2 system at 1 573 K 19) ϾCaO-SiO 2 -MnO(-MgO) at 1 623 K…”
Section: ϫmentioning
confidence: 99%
“…The studies of Nassaralla et al [14] and Tabuchi and Sano [15] indicated that BaO-BaF 2 slags were very effective for the dephosphorization of iron under either oxidizing or reducing conditions. Later, Liu et al [16] found that the replacement of BaO with CaO or MgO in BaO-BaF 2 -MnO slags decreased the phosphate capacity. Furthermore, the addition of CaF 2 to BaO-BaF 2 -MnO slags, lowered the BaO activity, which reduced the phosphate capacity of the BaO-containing slags.…”
Section: Introductionmentioning
confidence: 97%